2022
DOI: 10.1002/nbm.4711
|View full text |Cite
|
Sign up to set email alerts
|

Detection of tissue pH with quantitative chemical exchange saturation transfer magnetic resonance imaging

Abstract: Chemical exchange saturation transfer (CEST) magnetic resonance imaging (MRI) has emerged as a novel means for sensitive detection of dilute labile protons and chemical exchange rates. By sensitizing to pH-dependent chemical exchange, CEST MRI has shown promising results in monitoring tissue statuses such as pH changes in disorders like acute stroke, tumor, and acute kidney injury. This article briefly reviews the basic principles for CEST imaging and quantitative measures, from the simplistic asymmetry analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 210 publications
0
22
0
Order By: Relevance
“…Therefore, it will be helpful to optimize RF levels for ratiometric pH imaging to balance the labeling efficiency versus the DWS, which is critical to optimizing the ratiometric analysis at different field strengths. 31 Nevertheless, our study demonstrated that the RF amplitude-based CEST@2 ppm ratio is highly correlated with ischemic tissue acidosis at 4.7 T, which provides a potential alternative to the commonly used APTw MRI. This study evaluated RF amplitude-based endogenous CEST@2 ppm imaging in vivo and demonstrated it as a novel means of tissue pH imaging following acute stroke.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, it will be helpful to optimize RF levels for ratiometric pH imaging to balance the labeling efficiency versus the DWS, which is critical to optimizing the ratiometric analysis at different field strengths. 31 Nevertheless, our study demonstrated that the RF amplitude-based CEST@2 ppm ratio is highly correlated with ischemic tissue acidosis at 4.7 T, which provides a potential alternative to the commonly used APTw MRI. This study evaluated RF amplitude-based endogenous CEST@2 ppm imaging in vivo and demonstrated it as a novel means of tissue pH imaging following acute stroke.…”
Section: Discussionmentioning
confidence: 66%
“…For the same reason, the amide or GuanCEST signal cannot be directly correlated to the protein concentration. Extracting protein concentration from the CEST signal can be achieved by the quantitative CEST (qCEST) MRI, 73,74 which can correct the scaling introduced by the MTC or T 1 contrasts with the Bloch–McConnell equations or R 1ρ theory 75–78 …”
Section: Discussionmentioning
confidence: 99%
“…For the same reason, the amide or GuanCEST signal cannot be directly correlated to the protein concentration. Extracting protein concentration from the CEST signal can be achieved by the quantitative CEST (qCEST) MRI, 73,74 which can correct the scaling introduced by the MTC or T 1 contrasts with the Bloch-McConnell equations or R 1ρ theory. [75][76][77][78] In the current study, the PLOF background function was assumed with a simple linear function with a Lorentzian function, which was validated with the CrossBSA.…”
Section: Discussionmentioning
confidence: 99%
“…The QUASS calculation models the impacts of experimental parameters on the CEST signal. The equilibrium CEST effect can be calculated from the experimental measurements by solving the QUASS spin‐lock relaxation rate, despite not insufficiently long Ts and Td 56 …”
Section: Theorymentioning
confidence: 99%